Monsoon Effect at Flood Phenomena on 2002 and 2007 in DKI-JAKARTA - Gernowo, Rahmat (BERKALA FISIKA, 2009)
The monsoon effect one think especially represent to important matter as causes of floods happen in area of Jakarta. The research of convection pattern above area of DKI-Jakarta based on to existing perception data, which is expected will give the understanding of growth of convection cloud yield torrential rains and deliver floods in DKI-Jakarta on 2002 and 2007. The result of research into whereas in this research is obtained by the rain study of extreme in DKI-Jakarta. As rainfall data result of average from some stations is residing in DKI-Jakarta. The result of research is obtained by comparison analysis whereas, that cloud dynamics in DKI-Jakarta happened at around of December, January and February, where periodicity of monsoon takes place. Keywords: Monsoon, flood and cloud dynamics.